Research and application of multi-frequency electromagnetic technology in real-time online characterization of steel microstructures and mechanical properties - Chen Zhang; Jialong Shen; Zhengbing Meng; Guangmu Liu; Lei Zhou (Scientific Reports)
Abstract Mechanical properties of steels are closely related to microstructures. However, in steel process there is a lack of effective online monitoring and characterized methods for steel microstructures and mechanical properties, giving rise to issues of low steel quality and high alloy costs (to ensure mechanical strength). In order to ensure the mechanical performance of steels, advanced characterization methods and measurement instruments are necessary for real-time online monitoring of the production process. In this study, electromagnetic responses on steel microstructures and mechanical properties are investigated. An online electromagnetic non-destructive characterization system for steel microstructures is developed. Relationships between microstructures and steel mechanical properties have been demonstrated through mechanical performance tests. Therefore, the electromagnetic non-destructive characterization system can be used for real-time online monitoring of mechanical properties of steels.